The Writing Public Participatory Knowledge Production in Enlightenment and Revolutionary France - Andrews Bond, Elizabeth (Cornell University Press, 2021)
Inspired by the reading and writing habits of citizens leading up to the French Revolution, The Writing Public is a compelling addition to the long-running debate about the link between the Enlightenment and the political struggle that followed. Elizabeth Andrews Bond scoured France's local newspapers spanning the two decades prior to the Revolution as well as its first three years, shining a light on the letters to the editor. A form of early social media, these letters constituted a lively and ongoing conversation among readers.